SAKTI application in strengthening accountability and transparency in financial management at BNN South Lampung Regency - Muhammad Ma’arif; Pesi Suryani (Enrichment : Journal of Management, 2023)
The use of web-based applications is urgently needed and a necessity to produce fast, precise, transparent, and accountable financial reports. This study aims to determine the role of the SAKTI application system in strengthening transparency and accountability of financial management at the BNN in South Lampung Regency. Qualitative descriptive is used by researchers as the method used in the research conducted. Observations, interviews, and literature studies were carried out in data collection. The application of SAKTI Application plays an important role in strengthening the transparency and accountability of financial management as the results shown in this research study.